COMMUNITY STRUCTUREOF BIVALVES IN PULO PANE WATERS SOSORGADONG DISTRICT CENTRAL TAPANULI REGENCY NORTH SUMATRA PROVINCE - Johen Esaripa Gultom; Gultom Gultom; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This research was conducted in February-April of 2019 in Pulo Pane waters of  Sosorgadong District in Central Tapanuli  Regency of North Sumatra Province. The aims are to determine the community structure of bivalves includes: Species, abundance, relative abundance, diversity index, uniformity index, dominance index, similarities index and patterns of distribution. Sampling was done by using line transect method at 3 stations. The result found 6 families with 6 species of bivalves namely Anadara antiquata, Trachycardium subrugosum, Atactodea sp., Crassostrea sp., Donax sp.and Polymesoda erosa. The abundance value was in the range of 3.87 to 9.80 Ind/m2. Diversity index values ranged from 0.73 to 0.79 is relatively low, whereas the uniformity index values ranged from 0.69 to 0.77 that was categorized in balance condition, dominance index values ranged from 0.48 to 0.64 indicating there was a species dominantly, similarity index values ranged between 91-100% indicating nearly similar pattern. The distribution value pattern ranged from 0-10 with a clumped distribution pattern. Keywords: bivalves, Community Structure, Pulo Pane